Sociodemographic and cardiovascular risk factors associated with severe obesity in girls - Pajuelo Ramírez, Jaime (2021)
Introduction: Severe obesity (SO) has been studied very little in Peru. Objective: To determine the prevalence of SO according to two diagnostic criteria and its relationship to socio-demographic and cardiovascular risk factors in the child population. Methods: BMI was used, defining as obesity at a value ≥ ≥ at 95p and SO at: ≥ 99p and ≥ 120% of 95p, respectively (n=2001). For dyslipidemias the following: hypercholesterolemia 200 mg/dL, C-HDL under ≤ 40 mg/dL, C non HDL high ≥ 145 mg/dL, High C-LDL ≥ 130 mg/dL and hypertriglyceridemia for children under 9 ≥ to 100 mg/dL and 10 to 19 years ≥ 130 mg/dL and insulin resistance (RI) with a HOMA-I ≥3.16 (n=344). Results: 31,5% were obese. 12,8% SO with the first criterion and 7,7% with the second criterion. In both SO criteria it had association with age groups (OR: 0,55 IC 0,4-0,89) and (OR: 0,62 IC 0,43-0,89). Alteration of lipids and RI it was more prevalent in SO. The first criterion found significant association with C-LDL and hypertriglyceridemia; and in the second with C-HDL and hypertriglyceridemia. Conclusions: SO affects most the ethereal group of 6 to 9 years, those born with a normal weight, those who had a family history and girls whose mother reported not having had any level of instruction.